The game mediated by technology: motivating element for meaningful learning - Mendoza González, Jaime Enrique
Objective: The article seeks to highlight the importance of the game mediated by technology in educational processes to present an approach to different strategies that strengthen the methodology and teaching-learning process. Materials and methods: The state of the art was divided into two phases: the first one is heuristics, documenting different sources of information; the second one is the hermeneutic phase based on the conceptualization of the problem, and a list of investigations, theorists, and interpretations about the subject and the point of views of different authors. Result and discussion: Society has undergone social and technological changes, and nowadays young people have demands that must be met, and the knowledge society has allowed access to large amounts of information, for this reason, it is important to rethink the way of teaching, the use of motivating strategies such as the game mediated by technology, contributes to the achievement of meaningful learning, at the same time to the changes in education, responding correctly to the needs of the students. Conclusions: When teaching, the teacher must ask himself why and for whom he teaches, since he must respond to the different needs of the students, creating a series of support strategies that allow the student to be directly linked to his training process, bringing it closer to reality through different scenarios, for the development of skills, abilities and the achievement of that lasting learning.